Association of individual resilience with organizational resilience, perceived social support, and job performance among healthcare professionals in township health centers of China during the COVID-19 pandemic - Wang, An-Qi; Tang, Chang-Hai; Song, Jia; Fan, Cheng-Xin; Wang, Wan-Chen; Chen, Zhong-Ming; Yin, Wen-Qiang (Frontiers in Psychology, 2022)
Background Primary healthcare professionals were overworked and psychologically overwhelmed during the COVID-19 pandemic. Resilience is an important shield for individuals to cope with psychological stress and improve performance in crises. This study aims to explore the association of individual resilience with organizational resilience, perceived social support and job performance among healthcare professionals in township health centers of China during the COVID-19 pandemic. Methods Data from 1,266 questionnaires were collected through a cross-sectional survey conducted in December 2021 in Shandong Province, China. Descriptive analysis of individual resilience, organizational resilience, perceived social support, and job performance was conducted. Pearson correlation analysis was used to examine the correlations among these variables, and structural equation modeling was performed to verify the relationships between these variables. Results The score of individual resilience was 101.67 ± 14.29, ranging from 24 to 120. Organizational resilience (β = 0.409, p < 0.01) and perceived social support (β = 0.410, p < 0.01) had significant direct effects on individual resilience. Individual resilience (β = 0.709, p < 0.01) had a significant direct effect on job performance. Organizational resilience (β = 0.290, p < 0.01) and perceived social support (β = 0.291, p < 0.01) had significant indirect effects on job performance. Conclusion During the COVID-19 pandemic, the individual resilience of healthcare professionals in township health centers was at a moderate level. Organizational resilience and perceived social support positively affected individual resilience, and individual resilience positively affected job performance. Furthermore, individual resilience mediated the effect of organizational resilience and perceived social support on job performance. It is recommended that multiple stakeholders work together to improve the individual resilience of primary healthcare professionals.